2015
DOI: 10.1038/srep16227
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Outcomes Differ with Capsulorhexis Sizes after Pediatric Cataract Surgery: A Randomized Controlled Trial

Abstract: Capsular outcomes of anterior/posterior capsulorhexis opening (ACO/PCO) are essential for performing a secondary in-the-bag intraocular lens implantation. To compare the capsular outcomes with different primary capsulorhexis sizes, Thirty-eight eligible patients (45 eyes) were randomly assigned to three groups by anterior capsulorhexis diameter (Group A: 3.0–3.9, Group B: 4.0–5.0, and Group C: 5.1–6.0 mm). The areas of ACO/PCO and posterior capsule opening opacity (PCOO) as primary outcomes, while, the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Some studies described its use in pediatric cataract surgery for both the anterior and posterior capsule and reported no complications 32, 33. The problem with this method is that when we are doing capsulotomy by radio-frequency, it leaves some small tags behind, and the rhexis edge is not as sharp as a manual tear 34, 35, 36…”
Section: Resultsmentioning
confidence: 99%
“…Some studies described its use in pediatric cataract surgery for both the anterior and posterior capsule and reported no complications 32, 33. The problem with this method is that when we are doing capsulotomy by radio-frequency, it leaves some small tags behind, and the rhexis edge is not as sharp as a manual tear 34, 35, 36…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported PEX syndrome as a major risk factor for late IOL-capsular bag dislocation [ 2 , 3 , 9 , 54 ]. Capsular and anterior capsule openings were not analyzed in these studies, but capsular contraction and phimosis occlusion of the capsulorhexis opening after cataract surgery is a well-known characteristic of PEX syndrome [ 18 , 34 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the group with an average sized capsulorrhexis, the results of the same visits were an initial size of 15.22 mm 2 , then 13.43 mm 2 in the 1 st month and 12.79 mm 2 in the 6 th month, with the percentage reduction being 12.92 % and 15.95 %, respectively. In the group with the largest initial capsulorrhexis (22.92 mm 2 ), the reduction after 1 month was up to 20.86 mm 2 (8.88 %), and 20.49 mm 2 (10.55 %) 6 months post-surgery (Lin et al, 2015). The capsulorrhexis of the study patients was not enlarged, as the author's view is that this is an additional manipulation which can deepen an already weakened zonular defect or damage preserved zonules, aggravating the post-surgery outcome prognosis in this way.…”
Section: Shah Et Al Reported About 59 Cases Of Traumatic Subluxated Lenses In Larkanamentioning
confidence: 89%